Live-work units in subarctic climate as a part of sustainable city development : A design proposal - Ohls, Ingemar (Luleå tekniska universitet, Arkitektur och vatten, 2018)
Today there is a wish from building entrepreneurs to be able to have other activities than traditional commercial areas on the street level in the residential housing while keeping the open store front windows facade. Another challenge today in development of cities are partially to maintain a socially sustainable city. A mix of housing,commercial, entertainment, and services make the area become more attractive to both men and women, entrepreneurship and civil society. By mixing the use there is a possibility to reduce segregation and strengthen a city’s capacity to build unity; social development. Live-work units can meet both these demands. The purpose of this master thesis is to illustrate how so called live-work units could be organized in a block in an urban environment. Live-work units are a new phenomenon in Sweden and, therefore, this study partially focuses on describing this type of living and its special requirements. A methodology is proposed for identifying if a location is suitable for live-work units and for what type of units; furthermore, parameters and regulations affecting the usage of live-work units are described and a method for design is proposed.